2022
DOI: 10.1111/jrh.12726
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐urban differences in monkeypox behaviors and attitudes among men who have sex with men in the United States

Abstract: Purpose: An outbreak of the monkeypox virus has been documented in the United States with most cases occurring among gay, bisexual, and other men who have sex with men (MSM). As monkeypox cases increase among relatively rural states, current public health messaging may not resonate with rural at-risk populations. Given this, there is a need to assess potential rural-urban differences in monkeypox behaviors and attitudes among MSM. Methods: A total of 582 eligible MSM completed an online cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Similar to other qualitative research among MSM, participants conveyed that condoms were no longer used routinely, 28 although encouragingly, they reported that other STI prevention strategies were desired. In other studies, the HBM has been used-including among MSM-to explain the uptake of health interventions such as vaccines for STIs, [29][30][31] and the use of HBM in this study yielded valuable information about BMSM's perceptions of prevention strategies and inclination to engage in these strategies in the future. Participants were generally willing to engage in all strategies presented to them, and our findings revealed important considerations and caveats for these strategies.…”
Section: Discussionmentioning
confidence: 85%
“…Similar to other qualitative research among MSM, participants conveyed that condoms were no longer used routinely, 28 although encouragingly, they reported that other STI prevention strategies were desired. In other studies, the HBM has been used-including among MSM-to explain the uptake of health interventions such as vaccines for STIs, [29][30][31] and the use of HBM in this study yielded valuable information about BMSM's perceptions of prevention strategies and inclination to engage in these strategies in the future. Participants were generally willing to engage in all strategies presented to them, and our findings revealed important considerations and caveats for these strategies.…”
Section: Discussionmentioning
confidence: 85%
“…While the importance and benefit of crafting public health policy and messaging to avoid ever stigmatizing any group cannot be understated, it is also worth noting that the 2022 mpox outbreak ended fairly swiftly which may be in part due to public understanding of mpox as a disease primarily affected GBMSM. An August 2022 survey of MSM showed that 90.4% did not ever think they had mpox and 97.6% had not been tested, but 22.9% had already received mpox vaccine and 56.0% had changed their sexual behavior due to the outbreak [ 24 ]. Another August survey of 824 MSM found that number of sex partners, one-time sexual encounters, and sex with partners met on dating apps or at sex venues was reduced in 48%, 50%, and 50% since learning about the mpox outbreak [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future outbreaks may inform the psychological processes underlying the relationship between education, political ideology, and preferences for government intervention in the case of public health crises. For example, strong uptake of the Mpox vaccine in the gay male community, which was most affected by the recent outbreak, contrasts strongly with very weak vaccination rates among the Hasidic Jewish communities in Rockland County, New York, which has witnessed an emergence of the community spread of polio, with at least one paralytic case, for the first time since 1979 (Feemster & Szipszky, 2020; Owens & Hubach, 2023).…”
Section: Discussionmentioning
confidence: 99%